Menerapkan Metode Inquiri Untuk Meningkatkan Hasil Belajar IPA Siswa Di SMP Negeri 185 Jakarta - Jarukhi Jarukhi; Maria Dewati; Irnin Agustina Dwi Astuti (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2020)
This research is to improve science learning outcomes using the inquiry method of students of class VII-3 SMP Negeri 185 Jakarta. The application of inquiry learning that focuses on the center of the student learning process and the student's thought process is expected to change students' interest in learning and activities in class, which in turn will affect student learning outcomes towards science material with the type of material. The data analysis technique in this research is data analysis which includes data from the observation results of the implementation of inquiry learning, pretest and posttest data for each cycle. Based on the results of the research conducted, it can be seen that the results of learning science with the inquiry method of students of class VII-3 SMP Negeri 185 Jakarta have increased significantly. This is evidenced by the proportion of student learning completeness, namely pre-cycle to cycle 1, an increase of 6.9%, an increase from cycle I to cycle II of 66.67%, and an increase from pre-cycle to cycle II. 73.57%.This research is to improve science learning outcomes using the inquiry method of students of class VII-3 SMP Negeri 185 Jakarta. The application of inquiry learning that focuses on the center of the student learning process and the student's thought process is expected to change students' interest in learning and activities in class, which in turn will affect student learning outcomes towards science material with the type of material. The data analysis technique in this research is data analysis which includes data from the observation results of the implementation of inquiry learning, pretest and posttest data for each cycle. Based on the results of the research conducted, it can be seen that the results of learning science with the inquiry method of students of class VII-3 SMP Negeri 185 Jakarta have increased significantly. This is evidenced by the proportion of student learning completeness, namely pre-cycle to cycle 1, an increase of 6.9%, an increase from cycle I to cycle II of 66.67%, and an increase from pre-cycle to cycle II. 73.57%.